Chronic exposure to lipopolysaccharides as an in vitro model to simulate the impaired odontogenic potential of dental pulp cells under pulpitis conditions - Igor Paulino MENDES SOARES; Caroline ANSELMI; Maria Luiza Barucci Araujo PIRES; Rafael Antonio de Oliveira RIBEIRO; Maria Luísa LEITE; Diana Gabriela SOARES; Carlos Alberto DE SOUZA COSTA; Josimeri HEBLING (University of São Paulo, 2023)
Abstract Simulating a bacterial-induced pulpitis environment in vitro may contribute to exploring mechanisms and bioactive molecules to counteract these adverse effects. Objective To investigate the chronic exposure of human dental pulp cells (HDPCs) to lipopolysaccharides (LPS) aiming to establish a cell culture protocol to simulate the impaired odontogenic potential under pulpitis conditions. Methodology HDPCs were isolated from four healthy molars of different donors and seeded in culture plates in a growth medium. After 24 h, the medium was changed to an odontogenic differentiation medium (DM) supplemented or not with E. coli LPS (0 - control, 0.1, 1, or 10 µg/mL) (n=8). The medium was renewed every two days for up to seven days, then replaced with LPS-free DM for up to 21 days. The activation of NF-κB and F-actin expression were assessed (immunofluorescence) after one and seven days. On day 7, cells were evaluated for both the gene expression (RT-qPCR) of odontogenic markers (COL1A1, ALPL, DSPP, and DMP1) and cytokines (TNF, IL1B, IL8, and IL6) and the production of reactive nitrogen (Griess) and oxygen species (Carboxy-H2DCFDA). Cell viability (alamarBlue) was evaluated weekly, and mineralization was assessed (Alizarin Red) at 14 and 21 days. Data were analyzed with ANOVA and post-hoc tests (α=5%). Results After one and seven days of exposure to LPS, NF-κB was activated in a dose-dependent fashion. LPS at 1 and 10 µg/mL concentrations down-regulated the gene expression of odontogenic markers and up-regulated cytokines. LPS at 10 µg/mL increased both the production of reactive nitrogen and oxygen species. LPS decreased cell viability seven days after the end of exposure. LPS at 1 and 10 µg/mL decreased hDPCs mineralization in a dose-dependent fashion. Conclusion The exposure to 10 µg/mL LPS for seven days creates an inflammatory environment that is able to impair by more than half the odontogenic potential of HDPCs in vitro, simulating a pulpitis-like condition.